Computer simulation study of polydispersity effect on the phase behavior of short diblock copolymers. (25th July 2016) - Jiao, Gui-Sheng; Li, Yue; Qian, Hu-Jun; Lu, Zhong-Yuan
Abstract: Recent progress in producing short chain length diblock copolymers facilitates the fabrication of block copolymer nanostructures with extremely small feature sizes. In this work, phase diagrams for monodisperse, one-sided and two-sided polydisperse short diblock copolymer melts are constructed using dissipative particle dynamics (DPD) simulations. Detailed comparisons are carried out between these systems to elucidate the influence of chain length polydispersity on the phase behavior of short diblock copolymers. In particular, we find an unexpected stability of a bicontinuous structure over a wide composition range between 0.7 <  f  ≤ 0.8 in one-sided polydisperse system, where f is the volume fraction of the polydisperse component. In the case of the two-sided polydisperse system, due to the presence of highly asymmetrical block copolymers and the pulling-away of short blocks of these molecules into opposite domain, an up-shift is found in the order–disorder transition boundary to larger χN values over the composition range we investigated. Graphical abstract: Highlights: Phase diagrams for monodisperse, one-sided and two-sided polydisperse short diblock copolymer melts are constructed. An unexpected stability of a bicontinuous structure over a wide composition range for polydisperse component between 0.7 <  f  ≤ 0.8 is found in one-sided polydisperse system. For the two-sided polydisperse system, an overall up-shift is found in the order-disorder transition boundary to larger χ N values due to the presence of highly asymmetrical block copolymers and the dissolve of short blocks of these molecules into the opposite domain.